2021
DOI: 10.1111/jori.12368
|View full text |Cite
|
Sign up to set email alerts
|

Insurability of pandemic risks

Abstract: This paper analyzes the scope of the private market for pandemic insurance. We develop a framework that explains theoretically how the equilibrium price of pandemic insurance depends on accumulation risk, covariance between pandemic claims and other claims, and covariance between pandemic claims and the stock market performance. Using the natural catastrophe (NatCat) insurance market as a laboratory, we estimate the relationship between the insurance price markup and the tail characteristics of the loss distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…(ii) Liquid-asset rate: According to the report of Gründl et al, life insurers hold relatively high liquid assets (i.e., more than 50% of the asset portfolio) due to their long-term liability-driven investment for asset-liability matching management [ 28 ]. The limitation of the liquid-asset rate falls between the green loan rate and the guaranteed rate.…”
Section: Methods and Datamentioning
confidence: 99%
“…(ii) Liquid-asset rate: According to the report of Gründl et al, life insurers hold relatively high liquid assets (i.e., more than 50% of the asset portfolio) due to their long-term liability-driven investment for asset-liability matching management [ 28 ]. The limitation of the liquid-asset rate falls between the green loan rate and the guaranteed rate.…”
Section: Methods and Datamentioning
confidence: 99%
“…However, the boundary of insurability of specific risk is not set in stone. Like floods, terrorism and earthquakes, which are now fully or partially covered by insurance, pandemics are in the class of catastrophic risks (Gründl et al 2021 ). As the American Academy of Actuaries (AAA) states, “pandemic risk is more similar to the catastrophic risks covered by programs like the Terrorism Risk Insurance Program and the National Flood Insurance Program than to risks normally insured by the commercial insurance market” (American Academy of Actuaries 2020 ).…”
Section: Insurability Of Pandemic Risksmentioning
confidence: 99%
“…At first sight, so we will argue, the COVID-19 crisis might present a situation that does not comfortably fit either of the compensation or governance functions. Property insurers, especially those covering business interruption, maintained that private insurance coverage for economic losses caused by pandemics should be limited, otherwise they would go broke and the industry would be destroyed (Gründl et al 2021 ; Hartwig et al 2020 ). Insurers have consistently denied coverage, leading to substantial insurance litigation, 2 as they apparently consider pandemic-related losses (more particularly losses due to business interruption) uninsurable.…”
Section: Introductionmentioning
confidence: 99%
“…Third, study the loss distribution of the insurance industry and the application of policy tools under the influence of the epidemic. Gründl et al ( 13 ) analyzed inter temporal risk-sharing scenarios using high-frequency data tracking the economic impact of the COVID-19 pandemic in the United States, and argued that the expected gap in the distribution of epidemic losses could be reduced by 50%. Babuna et al ( 14 ) concluded that the trend is an economic recession with reduced profits and increased claims.…”
Section: Literature Reviewmentioning
confidence: 99%